A qualitative investigation of influences on occupational therapists' research involvement in Ireland. (April 2023) - Dwyer, Christopher P; Keane, Alexandra; Casey, Dympna; Rogers, Fionnuala M; Hynes, Sinéad M
Background: To fulfil the desire for evidence-based practice, there is impetus for occupational therapy (OT) to make research a priority and to encourage research engagement. Purpose: This study's aim was to explore occupational therapists' reasons for and for not getting involved in research and to determine potential barriers and enablers to engaging in research. Methods: Three focus groups were conducted with five participants each. Data were thematically analysed. Findings: Occupational therapists' reasons for expressing interest in getting involved in research were having an interest in the condition and/or the symptoms being studied; promoting client support and service development; and 'upskilling'. Three themes emerged from the thematic analysis: (1) motivation to get involved in research can be influenced; (2) 'firefighting': barriers and organisational culture; and (3) The nature of research needs consideration from an occupational therapist perspective. Implications: Findings suggest that though occupational therapists are able to get involved in research, it remains that there are difficulties in doing so (e.g., organisational culture); and such difficulties may outweigh both reasons and enablers to such involvement. Reasons for expressing interest, enablers, barriers and the relationships among them warrant further investigation and consideration with respect to involving occupational therapists in research.